2021
DOI: 10.1186/s12943-020-01297-0
|View full text |Cite
|
Sign up to set email alerts
|

Two nanoformulations induce reactive oxygen species and immunogenetic cell death for synergistic chemo-immunotherapy eradicating colorectal cancer and hepatocellular carcinoma

Abstract: Background FOLFOX is a combinational regimen of folinic acid (FnA, FOL), fluorouracil (5-Fu, F) and oxaliplatin (OxP, OX), and has been long considered as the standard treatment of colorectal cancer (CRC) and hepatocellular carcinoma (HCC). Recent developments of nano delivery systems have provided profound promise for improving anticancer efficacy and alleviating side effects of FOLFOX. Previously, a nanoformulation (termed Nano-Folox) containing OxP derivative and FnA was developed in our lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(49 citation statements)
references
References 66 publications
0
49
0
Order By: Relevance
“…It must be borne in mind that the identified features of ICD are only “thin end of the wedge”, therefore, future investigation of ICD hallmarks is of critical importance for progress in the validation of emerging ICD inducers. In addition, the hepatic metastasis is known as the commonest form of distant metastasis in CRC, therefore, therapeutic efficacy of “targeted co-formulation + PD-L1 blockade” strategy will be assessed using mice with experimental CRC liver metastases 85 , in order to confirm the potential for the treatment of CRC liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It must be borne in mind that the identified features of ICD are only “thin end of the wedge”, therefore, future investigation of ICD hallmarks is of critical importance for progress in the validation of emerging ICD inducers. In addition, the hepatic metastasis is known as the commonest form of distant metastasis in CRC, therefore, therapeutic efficacy of “targeted co-formulation + PD-L1 blockade” strategy will be assessed using mice with experimental CRC liver metastases 85 , in order to confirm the potential for the treatment of CRC liver metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-PD-L1 checkpoint blockade therapy has been proven to benefit the survival of HCC patients and is listed as an adjuvant management strategy for advanced HCC. [45][46][47] However, its use is often limited because the separate application often induces drug resistance in tumor cells, and checkpoint blockade is often ineffective in HCC with low PD-L1 expression. Therefore, we tried to combine BAT NPs with anti-PD-L1 therapy to protect and deliver both antibodies simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that radiotherapy can be utilized to activate the immune system by inducing immunogenic cell death (ICD), an immune response against the antigens of dead or dying tumor cells [339]. ICD-associated damage via ROS production could possibly promote the activation and migration of dendritic cells to prime T cells for systemic anti-tumor immune responses [340,341]. However, radiation-stimulated immune responses have shown limited efficacy, particularly when tumors exhibit low X-ray absorption and energy deposition capacities [342,343].…”
Section: Nanomaterials To Improve and Augment Rtmentioning
confidence: 99%